MT-TiCN gradient coating of hard alloy cutter and preparation method of MT-TiCN gradient coating

By constructing an MT-TiCN gradient coating on cemented carbide cutting tools, the problems of high internal stress and insufficient adhesion of traditional TiCN coatings are solved, achieving comprehensive performance of high hardness, good toughness and wear resistance, and extending the tool life.

CN121380899APending Publication Date: 2026-01-23HUNAN FUOU TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511581731.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Traditional CVD-prepared TiCN coatings suffer from high internal stress and insufficient adhesion to the substrate due to their uniform composition, making it difficult to achieve both high hardness and good toughness, thus limiting their application in complex processing.

Method used

The MT-TiCN gradient coating structure is adopted, which includes a TiN base layer, an MT-TiCN gradient layer, a transition layer and an Al2O3 layer. By controlling the C/N atomic ratio to be distributed in a gradient along the coating thickness direction, the internal stress is reduced and the bonding strength is improved.

Benefits of technology

It significantly improves the bonding strength between the coating and the substrate, enhances the toughness and wear resistance of the coating, and extends the service life of the cutting tools.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121380899A_ABST
    Figure CN121380899A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of hard alloy surface engineering, and particularly relates to an MT-TiCN gradient coating of a hard alloy cutter and a preparation method of the MT-TiCN gradient coating. The coating sequentially comprises a TiN bottom layer, an MT-TiCN gradient layer, a transition layer and an Al2O3 layer from inside to outside, wherein the C / N atomic proportion of the MT-TiCN gradient layer is in gradient distribution from rich N to rich C in the thickness direction. The coating is prepared through a medium-temperature chemical vapor deposition process, the internal stress of the coating is effectively relieved, and the bonding strength, toughness and wear resistance of the coating and a matrix are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of cemented carbide surface engineering, and particularly relates to a cemented carbide tool MT-TiCN gradient coating and a preparation method thereof. BACKGROUND

[0002] Cemented carbide tools are widely used in the field of mechanical processing due to their high hardness and wear resistance. In order to further improve their cutting performance, a hard coating is usually deposited on the surface of the tool, and TiCN coating is particularly valued due to its high hardness and good wear resistance.

[0003] At present, TiCN coating is mostly prepared by chemical vapor deposition (CVD) method. However, the TiCN coating obtained by traditional CVD process is usually a homogeneous structure with uniform composition. Such homogeneous coating has the following significant disadvantages: first, due to the difference in lattice constant and thermal expansion coefficient between the coating and the cemented carbide substrate, a large internal stress will be generated in the homogeneous coating during the cooling process after deposition, resulting in insufficient adhesion between the coating and the substrate; second, under harsh working conditions such as high-speed cutting or intermittent cutting, stress concentration easily leads to peeling or brittle fracture of the coating, which seriously affects the service life of the tool. In addition, the homogeneous structure of the coating is difficult to simultaneously consider high hardness and good toughness, which limits its application in complex processing.

[0004] Therefore, there is an urgent need in the prior art for a TiCN coating structure and a preparation method thereof which can effectively relieve internal stress, improve the adhesion between the coating and the substrate, and simultaneously have high hardness and good toughness. SUMMARY

[0005] In view of the problems of the traditional CVD prepared TiCN coating in the prior art, such as large internal stress, insufficient adhesion to the substrate, and difficulty in balancing hardness and toughness due to uniform composition, the present application provides an MT-TiCN gradient composite coating for cemented carbide tools and a preparation method thereof. The purpose is to effectively relieve internal stress by constructing a coating structure with gradient change in composition, and significantly improve the adhesion strength between the coating and the substrate, and the toughness and wear resistance of the coating as a whole.

[0006] In order to solve the above technical problems, the present application is implemented as follows: The present application provides a cemented carbide tool MT-TiCN gradient coating, which comprises a TiN bottom layer, an MT-TiCN gradient layer, a transition layer and an Al2O3 layer arranged in turn from the surface of the cemented carbide substrate outward; the atomic ratio of C and N in the MT-TiCN gradient layer is gradiently distributed along the thickness direction of the coating, and transitions from N-rich on the side close to the TiN bottom layer to C-rich on the side away from the substrate.

[0007] Further, the MT-TiCN gradient layer has a thickness of 8-10 microns.

[0008] Further, the MT-TiCN gradient layer has a grain structure of an elongated columnar crystal.

[0009] Further, the transition layer comprises HT-TiCN and TiCO.

[0010] The application also provides a method for preparing the MT-TiCN gradient coating of the cemented carbide tool, comprising the following steps: (1) Pretreatment of the substrate: cleaning, degreasing and rust removal of the cemented carbide substrate; (2) Deposition of the TiN bottom layer: deposition of the TiN bottom layer under the conditions of 880-960 ℃ and 140-180 mbar, using H2, N2 and TiCl4 as raw materials; (3) Deposition of the MT-TiCN gradient layer: deposition of the MT-TiCN gradient layer under the conditions of 850-900 ℃ and 40-80 mbar, using H2, N2, CO, HCl, CH4 and CH3CN as raw materials, and controlling the gas flow to make the C / N atomic ratio gradiently distributed from N-rich to C-rich along the thickness direction of the coating; (4) Deposition of the transition layer: deposition of the transition layer under the conditions of 980-1100 ℃ and 50-160 mbar, using H2, N2, TiCl4, HCl, CH4 and CO as raw materials, and the transition layer comprises HT-TiCN and TiCO; (5) Deposition of the Al2O3 layer: deposition of the Al2O3 layer under the conditions of 980-1100 ℃ and 50-100 mbar, using H2, HCl, CO, H2S, CO2 and Al as raw materials; (6) Cooling and purging: cooling to below 500 ℃ and purging with N2.

[0011] Further, in step (3), the deposition of the MT-TiCN gradient layer uses segmented control of the gas flow, specifically comprising: Section one: temperature 880 ℃, pressure 50 mbar, H2 50 L / min, N2 30 L / min; Section two: TiCl4 6 mL / min, CH3CN 1 mL / min, deposition for 30 min; Section three: H2 and N2 flow are adjusted to 70 L / min and 10 L / min, respectively; Section four: TiCl4 8 mL / min, CH3CN 2 mL / min, HCl 1.2 mL / min, deposition for 200 min.

[0012] Furthermore, in step (3), the gradient change of the C / N atomic ratio is achieved by controlling the CH3CN flow rate.

[0013] Furthermore, in step (4), the transition layer deposition includes first depositing HT-TiCN and then depositing TiCO.

[0014] Furthermore, in step (5), the Al2O3 layer deposition includes a nucleation stage and a growth stage.

[0015] Compared with the prior art, the present invention has the following significant advantages: (1) Strong bonding and low internal stress: By constructing a C / N composition gradient, the lattice parameters and thermal expansion coefficient of the coating form a smooth transition between the TiN bottom layer and the Al2O3 layer, like a "buffer zone", which significantly reduces the stress concentration at the interface, greatly improves the bonding strength between the coating and the substrate, and effectively prevents the coating from peeling off.

[0016] (2) Excellent overall performance: The MT-TiCN gradient layer is deposited under medium temperature conditions, resulting in a fine and dense columnar crystal structure. At the same time, it gives the coating high hardness and good toughness, making it less prone to brittle fracture under harsh working conditions such as intermittent cutting.

[0017] (3) Good structural integrity: The MT-TiCN gradient layer provides an excellent nucleation interface for the subsequent deposition of Al2O3 layer, ensuring the integrity and compactness of the entire multilayer coating system.

[0018] (4) Strong process controllability: By introducing CH3CN as a carbon and nitrogen source and precisely controlling its flow rate, the C / N ratio in the gas phase can be adjusted more flexibly and stably, thereby achieving an ideal gradient structure and breaking through the limitation of traditional gas gradients being difficult to control precisely. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort, wherein: Figure 1 The wear resistance test comparison chart provided by this invention; Figure 2 Microscopic morphology of the MT-TiCN gradient layer provided by this invention; Figure 3 Wear diagram of a conventional homogeneous TiCN-coated blade after 16 minutes of dry cutting, as provided by this invention; Figure 4The wear chart of the MT-TiCN gradient coating tool blade provided by the application after dry cutting for 16 minutes is shown. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the application will be clearly and completely described below with reference to the drawings in the embodiments of the application. Obviously, the described embodiments are some of the embodiments of the application, rather than all the embodiments of the application. Based on the embodiments in the application, all other embodiments obtained by a person of ordinary skill in the art without creative work fall within the protection scope of the application.

[0021] The terms "first", "second" and the like in the specification and claims of the application are used to distinguish similar objects, and are not used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged under appropriate circumstances, so that the embodiments of the application can be implemented in an order other than those illustrated or described herein, and the objects distinguished by "first", "second" and the like are generally of a kind and are not limited in number, for example, the first object can be one or more. In addition, "and / or" in the specification and claims indicates at least one of the connected objects, and the character " / ", generally indicates that the front and rear associated objects are in an "or" relationship.

[0022] The embodiments of the application provide a hard alloy tool MT-TiCN gradient coating, which is composed of a non-diffusion support layer and a cross-linking layer, the support layer is a polybenzimidazole film material, and the cross-linking layer is a multi-acid chloride material.

[0023] The application further provides a hard alloy tool MT-TiCN gradient coating, which comprises a TiN bottom layer, an MT-TiCN gradient layer, a transition layer and an Al2O3 layer arranged outward from the surface of the hard alloy substrate in sequence; the atomic ratio of C and N in the MT-TiCN gradient layer is gradiently distributed along the thickness direction of the coating, and the atomic ratio of C and N is transitioned from N-rich on the side close to the TiN bottom layer to C-rich on the side away from the substrate.

[0024] The thickness of the MT-TiCN gradient layer is 8-10 microns.

[0025] The crystal grains of the MT-TiCN gradient layer are in an elongated columnar crystal structure.

[0026] The transition layer comprises HT-TiCN and TiCO.

[0027] The application further provides a method for preparing the hard alloy tool MT-TiCN gradient coating, comprising the following steps: (1) substrate pretreatment: the hard alloy substrate is cleaned, degreased and derusted to ensure that the substrate surface is clean and free of impurities, so as to reduce the internal stress of the coating and ensure sufficient bonding strength; (2) TiN underlayer deposition: TiN underlayer is deposited at 880-960℃ and 140-180mbar with H2, N2 and TiCl4 as raw materials, which prepares for the deposition of subsequent coating; (3) MT-TiCN gradient layer deposition: MT-TiCN gradient layer is deposited at 850-900℃ and 40-80mbar with H2, N2, CO, HCl, CH4 and CH3CN as raw materials, and the C / N atomic ratio is controlled to be gradiently distributed from N-rich to C-rich along the thickness direction of the coating; by controlling the C / N atomic ratio to transit from N-rich to C-rich along the thickness direction of the coating, the thermal expansion coefficient of the coating gradually approaches that of the Al2O3 layer from inside to outside, so as to effectively relieve the internal stress concentration caused by thermal mismatch; (4) Transition layer deposition: Transition layer is deposited at 980-1100℃ and 50-160mbar with H2, N2, TiCl4, HCl, CH4 and CO as raw materials, and the transition layer comprises HT-TiCN and TiCO; by depositing the transition layer, the bonding strength between the TiCN and Al2O3 coating can be improved; (5) Al2O3 layer deposition: Al2O3 layer is deposited at 980-1100℃ and 50-100mbar with H2, HCl, CO, H2S, CO2 and Al as raw materials; the layer can effectively protect the multilayer composite coating and the cemented carbide substrate, and significantly improve the oxidation resistance thereof; (6) Cooling and purging: cooled to below 500℃ and purged with N2.

[0028] In step (3), the MT-TiCN gradient layer deposition is controlled by subsection. Section one: temperature 880℃, pressure 50mbar, H2 50L / min, N2 30L / min; Section two: TiCl4 6mL / min, CH3CN 1mL / min, deposition for 30min; Section three: H2 and N2 flow rate are adjusted to 70L / min and 10L / min respectively; Section four: TiCl4 8mL / min, CH3CN 2mL / min, HCl 1.2mL / min, deposition for 200min.

[0029] Further, the gradient change of C / N atomic ratio is realized by controlling the flow rate of CH3CN.

[0030] In step (4), the transition layer deposition comprises depositing HT-TiCN first and then depositing TiCO.

[0031] In step (5), the Al2O3 layer deposition includes a nucleation stage and a growth stage.

[0032] The preparation method of the MT-TiCN gradient coating for cemented carbide cutting tools provided by the present invention will be described in detail below with specific embodiments and comparative examples.

[0033] Example 1 This embodiment 1 provides a method for preparing an MT-TiCN gradient composite coating for a cemented carbide cutting tool (model YBC152A). The specific steps are as follows: Matrix pretreatment: The carbide insert substrate (model CNMG120408) is pretreated by cleaning, degreasing, and rust removal to ensure that the surface is clean and free of impurities.

[0034] Preprocessing stage: The pretreated substrate is placed in a chemical vapor deposition (CVD) reactor, and H2 and N2 are introduced to raise the temperature inside the furnace to 900~950℃ and maintain the pressure at 200~500mbar for preheating and atmosphere preparation.

[0035] TiN bottom layer deposition: Adjust the reactor temperature to 950℃ and the pressure to 150mbar.

[0036] H2 (flow rate 34.2 L / min), N2 (flow rate 1.7 L / min), and TiCl4 (flow rate 3.92 mL / min) were introduced, and the deposition time was 40 minutes to form a TiN underlayer on the substrate surface.

[0037] MT-TiCN gradient layer deposition: A segmented gas flow rate control method is used to construct a C / N composition gradient. Specific process parameters are as follows: Section 1: Adjust the temperature to 880℃ and the pressure to 50mbar, and introduce H2 (50L / min) and N2 (30L / min) to adjust the gas stratification state in the reaction chamber.

[0038] Section 2: Under the above temperature and pressure conditions, TiCl4 (6 mL / min) and CH3CN (1 mL / min) were introduced, and after 30 minutes of deposition, a nitrogen-rich TiCN structure began to form.

[0039] Section 3: Adjust the H2 flow rate to 70 L / min and reduce the N2 flow rate to 10 L / min to change the gas environment inside the cavity and prepare for the C-rich transition.

[0040] Stage four: TiCl4(8 mL / min), CH3CN (2 mL / min) and HCl (1.2 mL / min) were introduced, and the MT-TiCN layer was deposited for 200 minutes, so that the composition of the MT-TiCN layer gradually changed to C-rich.

[0041] Through the above steps, the MT-TiCN gradient layer with a thickness of about 8-10 μm was successfully prepared, and the C / N atomic ratio of the layer gradually changed from N-rich to C-rich from the bottom layer (close to TiN) to the surface layer (far from the substrate). The layer has a fine columnar crystal structure.

[0042] It should be noted that the MT-TiCN gradient layer acts as a "buffer zone". On the side close to the TiN bottom layer, the composition of the MT-TiCN layer is relatively N-rich, which better matches the lattice of the underlying material; on the side far from the substrate, the composition of the MT-TiCN layer gradually becomes C-rich, providing more favorable chemical and structural conditions for the Al2O3 layer. This gradual change mechanism means that the composition, lattice parameters and thermal expansion coefficient in the coating are gradually changed, which reduces the stress peak at the interface, reduces the formation of micro-cracks, and prolongs the service life of the tool.

[0043] In addition, the introduction of acetonitrile provides a more flexible and precise control means for adjusting the C / N ratio in the gas phase. By changing the flow rate of acetonitrile, the C / N ratio can be directly and smoothly changed from N-rich to C-rich, forming an ideal gradient structure.

[0044] Transition layer (HT-TiCN + TiCO) deposition: HT-TiCN deposition: adjust the temperature to 1020°C and the pressure to 60 mbar, introduce H2(34.2 L / min), N2(8 L / min) and TiCl4(3.2 mL / min), and deposit for 50 minutes.

[0045] TiCO deposition: adjust the pressure to 70 mbar, introduce H2(60 L / min), TiCl4(7 mL / min) and HCl(0.88 mL / min), and deposit for 30 minutes to complete the deposition of the transition layer.

[0046] Al2O3 layer deposition: Nucleation stage: adjust the temperature to 1020°C and the pressure to 60 mbar, introduce H2(60 L / min), CO2(2 L / min), HCl(1 L / min) and AlCl3(5.5 L / min), and react for 35 minutes to promote the formation of Al2O3 nuclei.

[0047] Growth stage: Adjust the pressure to 70 mbar, introduce H2 (70 L / min), CO2 (2.8 L / min), H2S (160 mL / min), HCl (2.5 L / min) and AlCl3 (10 L / min), and deposit for 120 minutes to allow the Al2O3 layer to grow fully.

[0048] Cooling and purging: After the deposition process is completed, the coated product is cooled to below 500°C in the furnace, and N2 is introduced for purging. Then it is taken out of the furnace to obtain the MT-TiCN gradient composite coated tool.

[0049] Performance testing The coated blade (PY152) prepared in this embodiment was compared with the company's existing products (PY151, PY251, PY351) and internationally advanced products (Sandvik GC4015, GC4025, GC4035, GC4225; Mitsubishi UE6010, UE6020) in a comparative test.

[0050] Test conditions: Material to be processed: 45# steel, hardness HB170-190.

[0051] Machine tools: HAAS SL-40 CNC machine tool, CK7525 CNC machine tool.

[0052] Cutting method: Dry cutting.

[0053] Test results: Wear resistance was compared at a cutting speed of 450 m / min, and the results are as follows: Figure 1 As shown.

[0054] Depend on Figure 1 It is evident that the wear resistance of the PY152 and PY252 cutting tools prepared by this invention is significantly better than that of the company's existing products and Mitsubishi products, and is comparable to that of Sandvik's high-end products.

[0055] X-ray diffraction analysis revealed that the percentages of C and N atoms in the MT-TiCN gradient layer of this embodiment were approximately 50.5% and 49.5% (PY152), respectively, indicating precise compositional control. See also... Figure 2 As shown, the morphology of MT-TiCN in the MT-TiCN gradient layer is as follows: from the longitudinal section, its structure is a slender columnar crystal. Some grains can penetrate the entire coating, forming a sword-shaped structure with a pointed top and a dividing line in the middle, resulting in fine fibrous grains. The thickness of the MT-TiCN coating is 8~10μm.

[0056] Comparative Example 1 The comparative example 1 uses a traditional homogeneous TiCN coating process (i.e. keeping the gas flow constant during the entire TiCN deposition process without gradient control) to prepare the comparative blade.

[0057] As shown in FIGS. 1 and 2, the test results show that the comparative blade has a significantly faster flank wear under the same cutting conditions, and is more prone to coating peeling or micro-cracks during high-speed intermittent cutting, and has a significantly lower service life than the gradient coating blade prepared by the embodiment of the present application. Figure 3 Figure 4 As shown in FIGS. 1 and 2, the test results show that the comparative blade has a significantly faster flank wear under the same cutting conditions, and is more prone to coating peeling or micro-cracks during high-speed intermittent cutting, and has a significantly lower service life than the gradient coating blade prepared by the embodiment of the present application.

[0058] In summary, the present application successfully prepares the MT-TiCN layer with a composition gradient structure by precisely controlling the MT-CVD process parameters, especially by using CH3CN and segmentally regulating the gas flow. The structure as a key "buffer zone" effectively coordinates the physical property differences between the layers, and finally obtains the hard alloy tool coating with high bonding strength, low internal stress, good wear resistance and long service life.

[0059] It should be noted that in this document, the terms "comprising", "including", or any other variant thereof are intended to cover non-exclusive inclusions, so that processes, methods, articles, or devices that include a series of elements not only include those elements, but also include other elements not explicitly listed, or inherent to such processes, methods, articles, or devices. Without more limitations, the element defined by the statement "including a…" does not exclude the presence of additional identical elements in the process, method, article, or device that includes the element.

[0060] In addition, it should be noted that the scope of the methods and systems in the embodiments of the present application is not limited to performing functions in the order shown or discussed, but can also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described methods can be performed in an order different from that described, and various steps can also be added, omitted, or combined. In addition, the features described with reference to certain examples can be combined in other examples.

[0061] The embodiments of the present application are described above in combination with the drawings, but the present application is not limited to the above specific embodiments, and the above specific embodiments are only illustrative, not limiting, and those skilled in the art can make many forms under the inspiration of the present application without departing from the purpose of the present application and the scope protected by the claims.​

Claims

1. A cemented carbide cutting tool with an MT-TiCN gradient coating, characterized in that, It includes a TiN underlayer, an MT-TiCN gradient layer, a transition layer and an Al2O3 layer arranged sequentially from the surface of the cemented carbide substrate outward; the atomic ratio of C and N in the MT-TiCN gradient layer is distributed in a gradient along the coating thickness direction, transitioning from N-rich side near the TiN underlayer to C-rich side away from the substrate.

2. The MT-TiCN gradient coating for cemented carbide cutting tools according to claim 1, characterized in that, The thickness of the MT-TiCN gradient layer is 8~10μm.

3. The MT-TiCN gradient coating for cemented carbide cutting tools according to claim 1, characterized in that, The MT-TiCN gradient layer has a slender columnar crystal structure.

4. The MT-TiCN gradient coating for cemented carbide cutting tools according to claim 1, characterized in that, The transition layer comprises HT-TiCN and TiCO.

5. A method for preparing an MT-TiCN gradient coating for cemented carbide cutting tools as described in any one of claims 1-4, characterized in that, Includes the following steps: (1) Substrate pretreatment: Cleaning, degreasing and rust removal of the cemented carbide substrate; (2) TiN bottom layer deposition: TiN bottom layer was deposited using H2, N2 and TiCl4 as raw materials under conditions of 880~960℃ and 140~180mbar. (3) MT-TiCN gradient layer deposition: Under the conditions of 850~900℃ and 40~80mbar, H2, N2, CO, HCl, CH4 and CH3CN are used as raw materials. By controlling the gas flow rate, the C / N atomic ratio is distributed from N-rich to C-rich along the coating thickness direction. (4) Transition layer deposition: Under conditions of 980~1100℃ and 50~160mbar, a transition layer is deposited using H2, N2, TiCl4, HCl, CH4 and CO as raw materials. The transition layer includes HT-TiCN and TiCO. (5) Al2O3 layer deposition: Al2O3 layer was deposited at 980~1100℃ and 50~100mbar using H2, HCl, CO, H2S, CO2 and Al as raw materials; (6) Cooling and purging: Cool to below 500°C and purge with N2.

6. The method according to claim 5, characterized in that, In step (3), the MT-TiCN gradient layer deposition employs segmented gas flow control, specifically including: Section 1: Temperature 880℃, pressure 50mbar, H2 flow rate 50L / min, N2 flow rate 30L / min; Section 2: Introduce TiCl4 at 6 mL / min and CH3CN at 1 mL / min, and allow to settle for 30 min; Section 3: Adjust the H2 and N2 flow rates to 70 L / min and 10 L / min respectively; Section 4: Introduce TiCl4 at 8 mL / min, CH3CN at 2 mL / min, and HCl at 1.2 mL / min, and allow for deposition for 200 min.

7. The method according to claim 5, characterized in that, In step (3), the gradient change of the C / N atomic ratio is achieved by controlling the CH3CN flow rate.

8. The method according to claim 5, characterized in that, In step (4), the transition layer deposition includes first depositing HT-TiCN and then depositing TiCO.

9. The method according to claim 5, characterized in that, In step (5), the Al2O3 layer deposition includes a nucleation stage and a growth stage.

Citation Information

Cited By

  • A gradient composition powder core wire for arc spraying and a method of preparing a gradient coating

    CN122629422A